La sindrome del Paesaggista: intervista a Cristina Castel Branco - Falqui, Enrico (Ri-Vista. Research for landscape architecture, 2015)
After the confirmation of European Convention on Landscape (2006), it became strictly urgent to define the role of Landscape Architect and to give an homogeneous acknowledgement of the professional activity in the matters of Territory’s Planning and Town Designing, in every European Country. A famous Portuguese Landscape Architect, Cristina Castel Branco, through this interview, explains which are the causes of such a delay to define a specific role af Landscape Architect as an indipendent and specialist activity from others that actually play the same role not having the proper cultural and scientific education to do so. In the opinion of Cristina Castel Branco, though, the main reasons are concerned about the different levels of education inside the Universities and Master Schools of any countries of Europe, because they can not assure an effective integration between the humanistic and Fine Arts Culture with the scientific and technological Culture.